Necrotizing fasciitis after central cenous catheter placement - Leibig, Nico; Hirche, Christoph; Kneser, Ulrich; Kremer, Thomas (Surgical infections, 2014)
Background: Necrotizing fasciitis (NF) can appear after various penetrating or non-penetrating skin lesions. This is the first reported case in which NF occurred after a central venous line placement. Because of intubation and sedation of the critically ill patient, only local conditions can indicate NF although other decisive symptoms, such as pain out of proportion to physical findings, are not evaluable.Methods: Case report and review of the literature.Results: A 71-y-old male patient was admitted to the intensive care unit after spine surgery due to post-operative delirium. Because of respiratory failure he had to be intubated and sedated. Ten days after central venous line placement in the right subclavian vein a reddening and swelling of the insertion site was observed but considered as extravasation. When aggravation of the local symptoms occurred, the suspected diagnosis of NF was made and a radical debridement was performed immediately. After a second-look operation, defect closure with a free-flap transfer and split-thickness skin grafting could be achieved.Conclusions: The first report on NF in a critically ill patient due to a subclavian central intravenous line aims to encourage checking for iatrogenic soft tissue condition in sedated intensive care patients. These patients may have a greater risk of developing NF, because they often have predisposing factors such as diabetes, end-stage renal failure, and immune suppression.
Gesehen am 23.10.2020